2005
DOI: 10.1002/casp.837
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Standard Story of indigenous rights in Aotearoa/New Zealand

Abstract: Word count including extracts: 6793Key words: Indigenous rights; Maori; Pakeha; discourse analysis; discrimination; racism; biculturalism Zealanders over Maori. The third submission works up the similarity between indigenous rights and general property rights, negotiating the relationship between equal treatment and self-determination to legitimise the claims. We argue that discursive research on discrimination should approach texts as contributions to a dialectics of racism and anti-racism. This is useful for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…Brash, 2004), qualitative responses and summaries of responses described in earlier work on 'race talk' in NZ (e.g. Kirkwood et al, 2005;Nairn & McCreanor, 1990;Sibley & Liu, 2004;Wetherell & Potter, 1992), and research on perceptions of history and the collective guilt (Doosje, Branscombe, Spears, & Manstead, 1998). Items were revised to give a balanced number of protrait and contrait statements, as the discourses from which items were adapted tended to be protrait in nature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brash, 2004), qualitative responses and summaries of responses described in earlier work on 'race talk' in NZ (e.g. Kirkwood et al, 2005;Nairn & McCreanor, 1990;Sibley & Liu, 2004;Wetherell & Potter, 1992), and research on perceptions of history and the collective guilt (Doosje, Branscombe, Spears, & Manstead, 1998). Items were revised to give a balanced number of protrait and contrait statements, as the discourses from which items were adapted tended to be protrait in nature.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we expected that conservative voters' attitudes would be heavily anchored in culturally mainstream representations of biculturalism and history (operationalised here at the individual level as historical negation), and thus be more resistant to change than those of liberal voters . Discourses that emphasise maintenance of a status quo favouring the dominant group are far more prevalent in NZ mass media than alternatives that emphasise affirmative action and historical redress to redistribute value in favour of the minority (see Kirkwood et al, 2005;Wetherell & Potter, 1992). Hence, in the language of social dominance theory, we expected a form of 'behavioural asymmetry', where conservative voters would express high levels of opposition to resource-specific aspects of bicultural policy regardless of condition (being effectively immune to more liberal arguments rarely encountered in mainstream media and everyday talk), whereas we predicted that liberal voters would be more open to an argument that emphasised the relevance of history for determining a just and fair basis for resource allocations and resource-related social policy.…”
Section: Studymentioning
confidence: 98%
“…This tradition includes the examination of white majority group members' talk in Great Britain, the United States and the Netherlands (van Dijk, 1993) and race talk among Australian university students (Augoustinos, Tuffin, & Every, 2005). Within New Zealand key studies have identified durable patterns in race relations talk (Nairn & McCreanor, 1991), highlighted the discursive delicacy and ambivalence involved in race talk (Wetherell & Potter, 1992), offered challenges to the view that colonisation is of historical relevance only (Kirkwood, Liu, & Weatherall, 2005), and examined the way political speeches construct identity, history and responsibility in contemporary debates over land issues (Kendall, Tuffin, & Frewin, 2005). The current analysis seeks to contribute to understandings of race relations in terms of positioning effects and constructions as they impact on indigenous interests.…”
Section: Discursive Psychology and Racismmentioning
confidence: 97%
“…One form of cultural knowledge that informs racism judgments are different representations of history (Kirkwood, Liu, & Weatherall, 2005). White Americans may have perceived less racism in the Katrina relief effort in part because they are less knowledgeable than African Americans about documented incidents of racism in response to past disasters (e.g., Mississippi flood of 1927; Barry, 1997;see Adams, O'Brien et al, 2006).…”
mentioning
confidence: 99%